Forecast of COVID-19 Cases in Indonesia with the Triple Exponential Smoothing Algorithm - Ruliyanta Ruliyanta; Endang Retno Nugroho (Universitas Nasional, 2020)
The Coronavirus (SARS-CoV-2), also known as COVID-19, has brought a worldwide threat to the living. The whole world is making extraordinary efforts to combat the spread of this deadly disease in terms of infrastructure, finances, data sources, protective equipment, life risk treatment, and several other resources. Artificial intelligence researchers focus their knowledge of expertise on developing mathematical models to analyze this epidemic situation using shared national data. To contribute to the welfare of the living community, this article proposes to utilize the Triple Exponential Smoothing algorithm to predict the development of COVID-19 throughout the country by utilizing real-time information from the Task Force for the Acceleration of Handling of Coronavirus Disease 2019 in Indonesia. Based on forecasting results, in Indonesia by the end of 2020, COVID-19 will continue to grow significantly, the number of confirmed COVID-19 people is 386,571 people with a death toll of 15,622.